Promising Herbal Strategies in the Treatment of Psoriasis - Prajapati, Arti; Usmani, Shazia; Chandra, Dinesh; Wahab, Shadma; Prakash, Om; Shukla, Nishi; Khatoon, Shabana (Current Functional Foods, 2026)
The incidence of Psoriasis has been recorded as around 125 million cases worldwide, which comprises of around 2-3% of the general population throughout the globe. Major complications coupled with the disease comprise of psoriatic arthritis, depression, and cardio syndrome, leading to compromised palliation of aggravated depreciation of Health. Contemporary strategies intervene only in symptomatic relief without complete cure and occasionally even lead to skin melanoma. Henceforth, this compilation reviews the diverse clinical features of this skin disease and discusses relevant therapeutic strategies and outcomes therein.An accumulated amount of evidence was obtained via relevant keywords from authentic databases viz. Web of Science, Science direct, and Scopus. A comprehensive exploration unveiled an imperative role of plant-derived therapeutics in combating side effects related to synthetic drugs. The data also exhibited an association between synthetic and natural alternatives where the role of combination strategies is indispensable, deduced by both in vitro and in vivo research. The clinical trial data also appeared to be encouraging with respect to herb-induced treatment and prevention of Psoriasis.
Keywords: clinical trial